Derivation and validation of a prediction rule for mortality of patients with respiratory virus-related pneumonia (RV-p score). (September 2020) - Chen, Liang; Han, Xiudi; Li, YanLi; Zhang, Chunxiao; Xing, Xiqian
Background: Respiratory viruses are important etiologies of community-acquired pneumonia. However, current knowledge on the prognosis of respiratory virus-related pneumonia (RV-p) is limited. Thus, here we aimed to establish a clinical predictive model for mortality of patients with RV-p. Methods: A total of 1431 laboratory-confirmed patients with RV-p, including 1169 and 262 patients from respective derivation and validation cohorts from five teaching hospitals in China were assessed between January 2010 and December 2019. A prediction rule was established on the basis of risk factors for 30-day mortality of patients with RV-p from the derivation cohort using a multivariate logistic regression model. Results: The 30-day mortality of patients with RV-p was 16.8% (241/1431). The RV-p score was composed of nine predictors (including respective points of mortality risk): (a) age ⩾65 years (1 point); (b) chronic obstructive pulmonary disease (1 point); (c) mental confusion (1 point); (d) blood urea nitrogen (1 point); (e) cardiovascular disease (2 points); (f) smoking history (2 points); (g) arterial pressure of oxygen/fraction of inspiration oxygen (Pa O2 /FiO2 ) < 250 mmHg (2 points); (h) lymphocyte counts <0.8 × 10 9 /L (2 points); (i) arterial PH < 7.35 (3 points). A total of six points was used as the cut-off value for mortality risk stratification. Our model showed a sensitivity of 0.831 and a specificity of 0.783. The area under the receiver operating characteristic curve was more prominent for RV-p scoring [0.867, 95% confidence interval (CI)0.846–0.886] when compared with both pneumonia severity index risk (0.595, 95% CI 0.566–0.624, p  < 0.001) and CURB-65 scoring (0.739, 95% CI 0.713–0.765, p  < 0.001). Conclusion: RV-p scoring was able to provide a good predictive accuracy for 30-day mortality, which accounted for a more effective stratification of patients with RV-p into relevant risk categories and, consequently, help physicians to make more rational clinical decisions. The reviews of this paper are available via the supplemental material section.